PERAN LOYALITAS PELANGGAN PADA MARKETING MIX TERHADAP KEPUTUSAN KONSUMEN - Sutianingsih Sutianingsih; Yasin Samodra (STIE Atma Bhakti, 2021)
This study aims to determine and analyze the effect of price, place, product and promotion on purchasing decisions and consumer loyalty at the Warung Special Sambal Sragen branch. The population in this research is the consumers in the Sragen special Sambel Warung who transact in the first week of March with a total of 450 consumers. The sample in this study amounted to 45 respondents with a random sampling technique method, namely random sampling. The analysis technique in this research is multiple linear regression path analysis, instrument test, linearity test and hypothesis testing which includes multiple linear regression, simultaneous test (F test), partial test (t test), and coefficient of determination. The results of the t-test in the first equation can be concluded that the variables of place, product and promotion have a positive and significant effect on purchasing decisions. While the price has a negative and insignificant effect on purchasing decisions. The results of the t-test on the second equation can be concluded that the variables of Price, Place and Product have a positive and significant effect on Loyalty. And the Promotion variable has a negative and insignificant effect on Loyalty. The total R2 value of 0.983 can be interpreted as a variation of Consumer Loyalty at the Sragen special chili shop explained by the variables Price, Place, potential, Product and Purchase Decision of 98.3% and the remaining 1.7% explained by other variables outside the research model as an example of service quality, environmental comfort, and so on.